GLUCOCORTICOID RECEPTOR‐RELATED GENES: GENOTYPE AND BRAIN GENE EXPRESSION RELATIONSHIPS TO SUICIDE AND MAJOR DEPRESSIVE DISORDER. Issue 6 (31st March 2016) - Yin, Honglei; Galfalvy, Hanga; Pantazatos, Spiro P.; Huang, Yung‐yu; Rosoklija, Gorazd B.; Dwork, Andrew J.; Burke, Ainsley; Arango, Victoria; Oquendo, Maria A.; Mann, J. John
Abstract : Introduction: We tested the relationship between genotype, gene expression and suicidal behavior and major depressive disorder (MDD) in live subjects and postmortem samples for three genes, associated with the hypothalamic‐pituitary‐adrenal axis, suicidal behavior, and MDD; FK506‐binding protein 5 (FKBP5), Spindle and kinetochore‐associated protein 2 (SKA2), and Glucocorticoid Receptor (NR3C1). Materials and Methods: Single‐nucleotide polymorphisms (SNPs) and haplotypes were tested for association with suicidal behavior and MDD in a live (N = 277) and a postmortem sample (N = 209). RNA‐seq was used to examine gene and isoform‐level brain expression postmortem (Brodmann Area 9; N = 59). Expression quantitative trait loci (eQTL) relationships were examined using a public database (UK Brain Expression Consortium). Results: We identified a haplotype within the FKBP5 gene, present in 47% of the live subjects, which was associated with increased risk of suicide attempt (OR = 1.58, t = 6.03, P = .014). Six SNPs on this gene, three SNPs on SKA2, and one near NR3C1 showed before‐adjustment association with attempted suicide, and two SNPs of SKA2 with suicide death, but none stayed significant after adjustment for multiple testing. Only the SKA2 SNPs were related to expression in the prefrontal cortex (pFCTX). One NR3C1 transcript had lower expression in suicide relative to nonsuicide sudden death cases ( b = −0.48, SE = 0.12, t = −4.02, adjusted P = .004). Conclusion: We have identified an association of FKBP5 haplotype with risk of suicide attempt and found an association between suicide and altered NR3C1 gene expression in the pFCTX. Our findings further implicate hypothalamic pituitary axis dysfunction in suicidal behavior.